Lipoarabinomannan-Induced Cell Signaling Involves Ceramide and Mitogen-Activated Protein Kinase - Sirkar, Madhumita (American Society for Microbiology, 2002)
Lipoarabinomannan (LAM) is a major cell wall-associated lipoglycan, produced in large amounts (15 mg/g of bacteria) in different species of mycobacteria. Our laboratory has previously reported that LAM from Mycobacterium smegmatis exerts its cytotoxic activity via inhibition of protein kinase C, a key signaling molecule inside the mononuclear cells (S. Ghosh, S. Pal, S. Das, S. K. Dasgupta, and S. Majumdar, FEMS Immunol. Med. Microbiol. 21:181-188, 1998). In this study we report that LAM from Mycobacterium tuberculosis induces a signal transduction pathway in favor of survivability of the host cells via the generation of ceramide, a novel second messenger. The endogenous ceramide level in mononuclear cells was found to be enhanced during LAM treatment. The effects of LAM on protein tyrosine phosphorylation in human peripheral blood mononuclear cells were examined. LAM enhanced the tyrosine phosphorylation of p42 mitogen-activated protein kinase and phosphoinositol 3-kinase (PI3 kinase) and dephosphorylation of stress-activated protein kinase. LAM-induced phosphorylation of p42 (extracellular signal-regulated kinase 2) was further enhanced by wortmannin, a PI3 kinase inhibitor. To examine whether these effects are due to elevation of endogenous ceramide, we exposed the cells to cell-permeative C(2)-ceramide exogenously and studied the activities of different protein kinases. Fluorescence-activated cell sorter analysis and morphological studies showed that LAM induces cell survival. Therefore, these results suggest the ability of LAM to induce ceramide in the altered signaling pathway and help in cell survival.